2005
DOI: 10.1177/0146167204271588
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Need for Closure and Support for Military Action Against Iraq: Moderating Effects of National Attachment

Abstract: A variety of studies suggest that a high need for closure—that is, a desire for knowledge that is clear, stable, and unambiguous as opposed to confusing or uncertain—may be associated with greater hostility toward relevant outgroups. Using international attitudes as the context, the authors examine the hypothesis that the relationship between the need for closure and support for military action against Iraq may be moderated by identification with the national ingroup. Specifically, it is expected that this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 32 publications
3
100
2
7
Order By: Relevance
“…Other studies have used cognitive factors such as need for closure (Federico, Golec, & Dial, 2005) and prior knowledge (Cohrs & Moschner, 2002) to investigate such attitudes. Group-level factors examining attitudes towards war include, for instance, national attachment, interests, and ethnocentrism (Federico et al, 2005;Herrmann et al, 1999;Liu et al, 2009;Louis & Taylor, 2002;Pratto, Glasford, & Hegarty, 2006), collective perceived vulnerability (Elcheroth, 2006;Spini, Elcheroth, & Fasel, 2008), perceived adversary's motivations and level of force used (Herrmann et al, 1999;Healy, Hoffman, Beer, & Bourne, 2002;Mann & Gaertner, 1991), the relative power of the countries in conflict (Herrmann et al, 1999), and the existence of explicit or implicit alliances (Healy et al, 2002;Mann & Gaertner, 1991;Pratto, Glasford, & Hegarty, 2006). However, only little research has experimentally studied the effect of the political characteristics of the countries involved in conflicts on attitudes towards military intervention (Healy et al, 2002;Herrmann et al, 1999;Mintz & Geva, 1993).…”
Section: Support For Military Interventionmentioning
confidence: 99%
“…Other studies have used cognitive factors such as need for closure (Federico, Golec, & Dial, 2005) and prior knowledge (Cohrs & Moschner, 2002) to investigate such attitudes. Group-level factors examining attitudes towards war include, for instance, national attachment, interests, and ethnocentrism (Federico et al, 2005;Herrmann et al, 1999;Liu et al, 2009;Louis & Taylor, 2002;Pratto, Glasford, & Hegarty, 2006), collective perceived vulnerability (Elcheroth, 2006;Spini, Elcheroth, & Fasel, 2008), perceived adversary's motivations and level of force used (Herrmann et al, 1999;Healy, Hoffman, Beer, & Bourne, 2002;Mann & Gaertner, 1991), the relative power of the countries in conflict (Herrmann et al, 1999), and the existence of explicit or implicit alliances (Healy et al, 2002;Mann & Gaertner, 1991;Pratto, Glasford, & Hegarty, 2006). However, only little research has experimentally studied the effect of the political characteristics of the countries involved in conflicts on attitudes towards military intervention (Healy et al, 2002;Herrmann et al, 1999;Mintz & Geva, 1993).…”
Section: Support For Military Interventionmentioning
confidence: 99%
“…Although studies by Federico et al (2005) and Golec et al (2005) have indicated the possibility that need for closure or structure would be positively related to support for military action against Iraq in our U.S.-student sample, we had no empirical basis for speculating about how need for closure or structure would relate to our remaining post-9/11 attitudes (i.e., support for restrictions on human rights, support for President George W. Bush) and beliefs (i.e., that Saddam Hussein supported terrorism). From a theoretical standpoint, we expected that participants who scored high on need for closure or structure would be more likely to approach the post-9/11 world from a position of reducing intragroup variability (i.e., increasing the internal consistency of attitudes and beliefs voiced by Americans) and maximizing intergroup differences (i.e., those between the U.S. and its purported enemies) as a way of ensuring epistemic security (see Kruglanski & Webster, 1996).…”
Section: Hypothesesmentioning
confidence: 99%
“…Recent work on national identity has increasingly advocated the existence of two distinct forms of in-group attachment (Chi Cui & Adams, 2002;Federico, Golec, & Dial, 2005). Whilst one aspect of national identity can be seen as a blind, militaristic and obedient attitude towards the state, an opposing aspect may question and constructively criticise it.…”
Section: National Identitymentioning
confidence: 99%
“…In this case, patriots may feel inclined to support charities that support the victims of war. As patriotism does not necessitate dominance over other countries (Akhter, 2007) and may result in a positive attitude towards international collaboration (Federico et al, 2005), those with a patriotic disposition may express a desire to help other countries in times of need. On the other hand, "patriotism is primarily focused on promoting the welfare of one's own nation" (Kemmelmeier & Winter, 2008, p. 863), which suggests that fellow nationals (and hence local or national level charities) may be deemed more worthy of financial support than other countries.…”
Section: Author Copymentioning
confidence: 99%